Dynamic Finite Element Analyses of the Primary System of the Atucha II NPP under Beyond Design Basis Earthquakes - Pecorari, Agustín (2017)
Atucha II Nuclear Power Plant (CNA II) is a pressurized heavy water reactor (PHWR) that started its commercial operation in May 2016. Construction began during 1980, and the design licensing base, agreed between the Responsible Entity (CNEA at that time) and the designer (KWU/Siemens), did not consider the double-ended guillotine break (DEGB) event in the primary pipe loop as a requirement of the emergency core cooling systems and reactor shutdown. Instead, a 10% loss of coolant of the cross section of the primary system, which would be equivalent to a surgeline DEGB (line connecting the primary system with the pressurizer), was considered. The Autoridad Regulatoria Nuclear (nuclear regulatory body of Argentina – ARN) entrusted the realization of an independent evaluation, to assess whether a DEGB caused by a beyond design basis event could be possible. A dynamic analysis of the Loop 2 of CNA II’s primary system was performed employing the finite element method (FEM) for a beyond design basis earthquake scene, i.e. an earthquake with a mean probability of exceedance of 10-6 per year, to evaluate the possibility of occurrence of a DEGB with critical preexisting areas with circumferential through-wall cracks in the primary system. The model utilized displacement time histories as input data, applied at the supporting points of major components (reactor pressure vessel, stream generator, main coolant pump, pressurizer), obtained by numerical integration of the acceleration time histories at such points, provided by the designer.